(untitled) (Research, Society and Development, 2020)
The objective of the present work was to carry out a historical analysis of 2,580 samples of industrial cheeses inspected in the Minas Gerais state - Brazil, concerning to the regulated physicochemical parameters: humidity, fat in dry matter, residual alkaline phosphatase enzyme activity and nitrate, during seven years. The parameters with highest prevalence of non-compliancy were fat in dry matter and activity of the alkaline phosphatase enzyme, driven by the Minas Frescal and Mozzarella varieties, respectively. There was also evidence of stability in the profile of non-compliancy in the evaluated period. Thus, actions to promote quality improvement focused in critical parameters would be strategic for a change in the level of quality and conformity of cheeses in the state. It was concluded that statistical tools applied in a complementary way to the inspection analyzes allowed to know and monitor the System, pointing out actions for its improvement, with focus on the promotion of food safety.